Peran Penyuluh dalam Meningkatkan Kapasitas Peternak melalui Penerapan Sistem Peternakan Berkelanjutan - Nurlina, Lilis; Yunasaf, Unang; Sulistyati, Marina; Alim, Syahirul; Mauludin, M. Ali (Universitas Galuh, 2025)
This research discusses the important role of livestock extension workers in enhancing the capacity of farmers to implement sustainable farming systems. Livestock Farming in Indonesia faces serious challenges, such as a decline in resource quality and dependence on conventional practices that are not environmentally friendly. One of the solutions introduced is the Low External Input Sustainable Agriculture (LEISA) system, which emphasizes the use of local resources and the minimization of external inputs. This research aims to explore the role of extension workers in assisting farmers to understand and adopt LEISA systems through technology transfer and technical guidance. The research method uses literature study with qualitative descriptive analysis, collecting data from various scientific journals, books, and related documents. The discussion results show that the extension worker plays the role of facilitator, motivator, communicator, and consultant. Although there are some limitations in the role of the extension worker as a facilitator and technology transfer agent, the roles of motivator and consultant are already quite effective. Extension workers also play an important role in promoting LEISA, assisting farmers in natural feed management, and utilizing livestock waste for agriculture. With the involvement of extension workers, it is hoped that farmers can increase livestock productivity while maintaining ecosystem balance and environmental sustainability.